How schools respond to and manage HIV and AIDS in the Limpopo Province - Maine, Samuel Mohau (My University, 2010)
This study investigates how schools respond to and manage HIV and AIDS within the Limpopo Province of South Africa. Twenty-two stakeholders (parents, learners, HODs’, teachers and principals) and two government (provincial) officials participated in the present study. Three schools were selected by means of purposive sampling. Qualitative data were collected by means of two methods, namely, interviews and document analysis. By way of data processing and analysis, the responses from three schools in the Limpopo Province were categorized for the purpose of the study. The study found that stakeholders do not seem to understand issues related to HIV and AIDS, and that there are no proper mechanisms in place to deal with these issues.
Thesis (M.Ed.) --University of Limpopo, 2004.
Keywords: HIV; AIDS